Predatory publishing – A cautionary for researchers - Kanchan , Tanuj (Journal of Indian Academy of Forensic Medicine, 2019)
Predatory publishing usually refers to publication of substandard journals or books etc. with the sole motive of minting money from, or at the cost of unsuspecting researchers. Thus, the idea of predatory publishing is to seek financial gains, and there are hardly any academic interests involved. The outcome is very obvious; release of journals and books with poor scientific content. The significant contrast between predatory and non-predatory publishing is based on the level of editorial and publishing efforts taken to check the quality of the content. It takes a lot of serious efforts on the part of the editorial and publishing team to ensure that quality articles with reliable and useful information only are passed on in the academic circles. It has been emphasized time and again to make researchers aware of the problems associated with predatory